Comparison of the accuracy of 15-5PH and 4330 steel parts produced by milling - Kuczmaszewski, Józef; Zaleski, Kazimierz; Matuszak, Jakub; Pałka, Tomasz; Mądry, Janusz (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
The accuracy of machine parts depend on numerous factors connected with: technological machines, tools, fixture clamps, the properties of workpiece material, cutting parameters, cutting fluids etc. This paper reports the results of a study investigating the accuracy of a series of objects with complex shape. The milling process was performed on a 3-axis machining center, Avia VMC-800HS. The measurements of geometric accuracy were made using the ZEISS Vista coordinate measuring machine. The examination of the repeatability of dimensional errors of the objects produced by milling led to determination of the values of tolerance which can be obtained under production conditions. Particular attention was paid to the errors of part quality as they may affect the assembly process. The accuracy of parts made of 15-5PH and 4330 steel was the compared. Accuracy class and dimensional deviation were determined. The results demonstrate that it is possible to ensure comparable accuracy of parts made of two different materials by selecting appropriate machining parameters. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)